Disparitas Putusan Peninjauan Kembali(Putusan Mahkamah Agung No. 109 Pk/Pid/2007 Dan No. 133 Pk/Pid/2011)dalam Kasus Pembunuhan Berencana Munir Said Thalib Dan Penggunaan Surat Palsu Oleh Terpidana Pollycarpus Budihari Priyanto - Muhammad Ulin Nuha; Burhanudin; Mara Sutan Rambe (JOURNAL of LEGAL RESEARCH, 2025)
This research analyzes the implementation of judicial review applications filed by both public prosecutors and defendants, focusing on the applicants’ legal grounds and the judges’ considerations in Supreme Court Decisions No. 109 PK/Pid/2007 and No. 133 PK/Pid/2011. The study employs a normative juridical approach, which examines relevant laws, legal principles, and scholarly doctrines to address the research questions systematically. The findings reveal that the right to file a judicial review is not limited to convicted persons but may also be exercised by public prosecutors. A judicial review may be accepted when judicial error occurs during the trial or when new evidence (novum) emerges that could significantly alter the verdict. The research further emphasizes that judges must act independently, free from external influence, and base their rulings solely on legal facts and judicial conviction.